Failed alternative development programs: an implementation analysis of coca supply-reduction programs in Bolivia. (1st January 2012) - Unlu, Ali; Kapti, Alican
This study evaluates the effectiveness of alternative-development programs in Bolivia and makes suggestions about how these programs can succeed. Several programs have been implemented in Bolivia over the past thirty-plus years, but little progress has occurred. Governments' political and economic frameworks may shape programs, but field implementation has rarely yielded the expected outcomes. This study examines the current policies of and evaluates national and international reports about the alternative-development programs implemented in Bolivia. Furthermore, political conflict between Bolivia and the USA may result in different expectations regarding coca policies. The success of alternative-development programs relies on the participation of local communities in utilising existing community structures rather than establishing new structures to transform local communities. In particular, the actions and commitment of individuals and leaders in local communities play a major role in program design and implementation.